2023
DOI: 10.17219/acem/157242
|View full text |Cite
|
Sign up to set email alerts
|

Previous chemotherapy can cause PONV

Abstract: Background.Although the treatment and mechanisms of postoperative nausea and vomiting (PONV) and chemotherapy-induced nausea and vomiting (CINV) are similar, the interactions between these 2 morbidities require more research. Objectives.In our prospective observational study, we investigated whether previous chemotherapy has an effect on PONV in breast cancer surgery. Materials and methods.One hundred and forty-eight female patients with the American Society of Anesthesiologists (ASA) physical status I or II, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…The occurrence of PONV is a fatal complication in patients with poor quality of anaesthetic awakening. It can cause acute respiratory obstruction in patients, resulting in aspiration pneumonia, destruction of alveolar surface cells by acid in the stomach, acute respiratory insufficiency, and further hypoxic acute cardiac arrest [4]. Studies have shown that the use of opioid analgesics increases the incidence of PONV in patients [5], but in the early days of Propofol's market launch, it was shown that Propofol at subanaesthetic doses significantly reduces the incidence of PONV [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of PONV is a fatal complication in patients with poor quality of anaesthetic awakening. It can cause acute respiratory obstruction in patients, resulting in aspiration pneumonia, destruction of alveolar surface cells by acid in the stomach, acute respiratory insufficiency, and further hypoxic acute cardiac arrest [4]. Studies have shown that the use of opioid analgesics increases the incidence of PONV in patients [5], but in the early days of Propofol's market launch, it was shown that Propofol at subanaesthetic doses significantly reduces the incidence of PONV [6,7].…”
Section: Introductionmentioning
confidence: 99%